2014
DOI: 10.1111/jwas.12159
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Koi Carp, Cyprinus carpio var. Koi (Linnaeus, 1758), Stocking Density and Nutrient Recycling With Spinach in an Aquaponic System

Abstract: Fish waste water nutrient recycling in an aquaponic system was studied under different stocking densities of Koi Carp, Cyprinus carpio var. koi, along with spinach, Beta vulgaris var. bengalensis. Fish growth performance, plant growth, nutrient dynamics, and nutrient removal and their dependence on different stocking densities, namely 1.4, 2.1, and 2.8, were observed, of the different combinations, fish stocked at 1.4 kg/m3 had the best growth. Percent nutrient removal (NO3–N, PO4–P, and K) was significantly h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 30 publications
4
20
2
Order By: Relevance
“…The optimal stocking density of koi carp (Cyprinus carpio var. koi) was at 1.4 kg/m (Hussain et al 2014), and the best weight gain and yield of Beta vulgaris var. bengalensis (spinach) was found with a water flow rate of 1.5 L/min (Hussain et al 2015).…”
Section: Fish Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal stocking density of koi carp (Cyprinus carpio var. koi) was at 1.4 kg/m (Hussain et al 2014), and the best weight gain and yield of Beta vulgaris var. bengalensis (spinach) was found with a water flow rate of 1.5 L/min (Hussain et al 2015).…”
Section: Fish Productionmentioning
confidence: 99%
“…It is interesting to note that plant growth and nutrient removal in koi (Cyprinus carpio var. koi) and gold fish (Carassius auratus) production (Hussain et al 2014(Hussain et al , 2015 with Beta vulgaris var. bengalensis (spinach) and water spinach (Ipomoea aquatica) increased linearly with a decrease in process water flow between 0.8 L/min and 1.5 L/min.…”
Section: Fish Productionmentioning
confidence: 99%
“…was found to achieve a nitrate removal rate of up to 90.9% (Lennard & Leonard, ), and spinach ( Beta vulgaris Linn.) was found to achieve nitrate reductions of 57.8%–80.0% (Hussain et al, ). In the T2 and T3 systems, an accumulation of PO 4 3− ‐P was observed over almost the entire trial, whereas PO 4 3− ‐P content decreased over time in the T1 system.…”
Section: Discussionmentioning
confidence: 99%
“…Low DO concentrations in co‐culture treatments may contribute to this reduction in fish growth. However, Hussain et al () reported that cohabitation with spinach could have a profound positive impact on the growth of Koi carp ( Cyprinus carpio Linnaeus). In addition, Portillo‐Clark et al () reported better growth parameters of shrimp when they were co‐cultured with green feather alga ( Caulerpa sertularioides Gmelin Howe) than when they were cultured alone.…”
Section: Discussionmentioning
confidence: 99%
“…For appropriate functioning, aquaponic systems require balancing multiple factors, including solution pH (Wongkiew et al, 2017a;Zou et al, 2016), plant and animal density (Buzby and Lin, 2014;Hussain et al, 2014Hussain et al, , 2015, solution flow rates (Hussain et al, 2015;Khater and Ali, 2015;Wongkiew et al, 2017b), economics (Quagrainie et al, 2018;Tokunaga et al, 2015), system configuration (Klemencic and Bulc, 2015;Monsees et al, 2017), and food safety considerations (Elumalai et al, 2017;Pantanella et al, 2015). Several authors have reviewed system types, management, and potential profitability of aquaponic production systems (Blidariu and Grozea, 2011;Lewis et al, 1978;Love et al, 2015).…”
Section: Physical Environmentmentioning
confidence: 99%